Development of eastern blotting technique for sennoside A and sennoside B using anti-sennoside A and anti-Sennoside B monoclonal antibodies - Morinaga O. (2014)
Introduction - Rhubarb, senna and sennoside-containing preparations are currently widely employed as purgatives. The major active components of these medications are sennoside A (SA) and sennoside B (SB). Objective - To develop an eastern blotting technique for the specific visualisation and easy determination of SA and SB in plant extracts for application in the standardisation and authentication of rhubarb and senna. Methodology - SA and SB were separated by TLC, transferred to a PVDF membrane, treated with 1-ethyl-3-(3′-dimethylaminopropyl)-carbodiimide hydrochloride solution and finally treated with bovine serum albumin (BSA). The resulting membrane-bound SA-BSA and SB-BSA conjugates were linked to anti-SA and anti-SB monoclonal antibodies (MAbs) and then to secondary antibodies labelled with peroxidase. SA and SB were detected by visualisation of the peroxidase reaction products. Results - The limit of detection of the eastern blotting was 62.5 ng for both sennosides. The method was applied to the immunohistochemical localisation of SA in fresh rhubarb root. Phloem and radiate wood were found to contain higher concentrations of SA compared with other tissues (pith and bud) in agreement with results obtained by ELISA. The concentrations of SA in the phloem, radiate wood, pith and bud were 64.4, 48.1, 15.0 and 1.8 ng/mg fresh weight, respectively. Conclusion - The technique described permitted the visualisation of small molecular weight compounds that had been bound to a membrane, using immunostaining. Owing to the specificity of the MAbs, the eastern blotting may prove to be a useful method for the identification of SA and SB in a background containing large amount of impurities. Copyright © 2009 John Wiley & Sons, Ltd.